Elephant’s activities elicited biodiversity disturbance in Omo Biosphere Reserve, Nigeria - AGBOOLA, OLUDARE; Molou, Andre Jacques; Akinsoji, Aderopo; Oyedeji, Stephen (Ecological Questions, 2022)
Disturbance by herbivores occurs in most of the natural ecosystems and influence species diversity and vegetation structure. This study compares the vegetation of elephant (disturbed) zone (EZ) and non-elephant (undisturbed) zone (NEZ) in the Omo biosphere reserve to assess the effect of elephant browsing on the vegetation. Woody species densities, basal area, importance value and species diversity were determined from twenty sampling plots (20 m x 20 m) established randomly each in the EZ and NEZ. The result of floristic composition shows more species were in the NEZ than EZ. The species diversity reduced by 3.3% in EZ. Sorensen index of similarity of the two communities was 62%. Celtis zenkeri (74.75) and Diospyros dendo (51.1) dominated the species in the EZ while Gmelina arborea (127.35) and Funtumia africana (16.63) were the dominant species in the NEZ. Browsing of elephants directly influence species composition, diversity and structure in the forest ecosystem leading to loss of biodiversity.